2001
DOI: 10.1590/s0066-782x2001000600002
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the prevalence of hypertension. Influence of sampling criteria

Abstract: Prevalence rates of hypertension differed a lot in the campaign sample and in the representative population sample, showing that the sampling criterion may influence assessment of risk factors and bias the association between risk factors and health aggravations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
2
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
1
11
2
7
Order By: Relevance
“…Nevertheless, only 27% of the hypertensive patients achieved blood pressure control, much lower than the desirable rate. This is similar to findings from other studies done in Brazil 6,8 and developed countries, 9,10 and it demonstrates the difficulty in achieving such a goal, which requires a search for new strategies and a change of approach to arterial hypertension. The higher the number of risk factors was, the poorer the hypertension control (Figure 5), probably because of the metabolic conditions associated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, only 27% of the hypertensive patients achieved blood pressure control, much lower than the desirable rate. This is similar to findings from other studies done in Brazil 6,8 and developed countries, 9,10 and it demonstrates the difficulty in achieving such a goal, which requires a search for new strategies and a change of approach to arterial hypertension. The higher the number of risk factors was, the poorer the hypertension control (Figure 5), probably because of the metabolic conditions associated.…”
Section: Discussionsupporting
confidence: 89%
“…1,2,3 Arterial hypertension is the most frequent treatable cardiovascular risk factor for death, 2,3,4 with prevalence ranging from 10 to 44% in different studies and countries. [4][5][6][7][8][9][10] Without symptoms in its initial stage, hypertension is generally diagnosed only when complications appear, thus causing significant losses in quality of life and increasing mortality rates. The costs for society are high, because this condition requires tertiary care and affects an economically active part of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also detected an association between hypertension and family history 3,5,20,21 . The positive association between hypertension and obesity was also observed in other studies 3,19,20,22 .…”
Section: Discussionmentioning
confidence: 85%
“…Population-based studies carried out in Brazil have shown that hypertension is a common disease, the prevalence of which is about 20% [2][3][4][5] . Today, cardiovascular diseases constitute the primary cause of death, representing roughly one-third of overall adult mortality in Brazil.…”
mentioning
confidence: 99%
“…With the increasing life expectancy of the general population, there is an increased prevalence of many chronic diseases, such as hypertension (Fuchs et al, 2001). Hypertension is characterized by maintenance of sustained high blood pressure levels (above 140/80 mmHg) (Chobanian et al, 2003;WHO, 2003), and it contributes significantly to serious complications such as stroke, myocardial infarction, congestive heart failure, and chronic renal failure (WHO, 1999;Chobanian et al, 2003;WHO, 2003;Kaplan, Opie, 2006;Thayer, Lane, 2007).…”
Section: Introductionmentioning
confidence: 99%